Inklusion digital! Chancen und Herausforderungen inklusiver Bildung im Kontext von Digitalisierung - Ferencik-Lehmkuhl, Daria; Huynh, Ilham; Laubmeister, Clara; Lee, Curie; Melzer, Conny; Schwank, Inge; Weck, Hannah; Ziemen, Kerstin (Dokumentarische Schulforschung, 2023)
Inclusion and digitization are about to decisively change society in several dimensions. This also includes (school) education. However, inclusive and digital education as central tasks of the education system have so far been discussed too rarely in combination. However, digital education is fundamental for enabling social participation and must therefore be a significant component of educational processes. The content of the anthology is based on selected contributions to the online conference ""Inklusion digital! - Opportunities and Challenges of Inclusive Education in the Context of Digitization"". The articles reflect the current discussions in teacher training and continuing education with regard to inclusion and digitization from the perspectives of subject didactics, subject sciences, educational science, and special education.